MANAGEMENT OF THE INVESTMENT POTENTIAL OF THE INSURANCE COMPANY - Shapoval , L.P.; Kaplenko, T.S.; Rudyk , V.K. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The article is devoted to the topical problem of effective management of the investment potential of the insurance company in the context of the need for changes in state legislation. The purpose of the article is a comprehensive assessment of the level of investment potential of the insurance company. A new model of state investment regulation of the insurance market is considered. The object of the study was the insurance company, as insurers are the largest investment institutions in the financial market. During the study, general scientific methods were used: systemic, complex – during the study of the process of managing the investment potential of the insurance company; coefficient, forecasting – to assess the investment activity of the insurance company; tabular and graphic method – to visualize the dynamics and structure of research indicators. Based on a comprehensive assessment of the investment activity of the insurance company, a sufficient level of its profitability was determined, but it was found that the main problem in managing the investment potential of the insurer is the low level of liquidity of assets. The reasons for their reduction are clarified and the directions of investment portfolio diversification are suggested. The conducted study suggests that the implementation of the new model of government regulation will improve the mechanism for managing the investment potential of the insurance company. This in turn requires legislative changes in accordance with EU guidelines